Cournot Oligopoly and Competitive Behaviour - Ruffin, R. J. (Review of Economic Studies, 1971)
Journal Article Cournot Oligopoly and Competitive Behaviour Get access R. J. Ruffin R. J. Ruffin University of Iowa Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 4, October 1971, Pages 493–502, https://doi.org/10.2307/2296692 Published: 01 October 1971